1983
DOI: 10.1227/00006123-198301000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Intradural Chondroma: A Case Report and Review of the Literature

Abstract: We present a rare case of intradural chondroma. Its clinical and radiological presentation, with special emphasis on the computed tomographic appearance, and its surgical management are discussed and compared to previously published reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 0 publications
0
48
0
Order By: Relevance
“…10,11 The age of patients reported in the literature ranges from 15 months to 60 years. [11][12][13][14] Several previous publications reported a slight female preponderance in intracranial chondromas. 14,15 In our group of 30 patients, patient age ranged from 16 years to 60 years and the mean age was 35.4 years.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…10,11 The age of patients reported in the literature ranges from 15 months to 60 years. [11][12][13][14] Several previous publications reported a slight female preponderance in intracranial chondromas. 14,15 In our group of 30 patients, patient age ranged from 16 years to 60 years and the mean age was 35.4 years.…”
Section: Discussionmentioning
confidence: 98%
“…8,11,[16][17][18][19][20] These disease-related chondromas may exhibit greater cytological atypia and cellularity and patients with Maffucci's syndrome have an increased risk of malignant 11,13 Most intracranial chondromas arise from the embryonic cartilaginous remnants of chondrogenic cells at the basilar synchondroses of the cranial base with a predilection for the spheno-ethmoid region, or in the paranasal sinuses with extension into the cranial cavity. 12,17,21,22 However, intracranial chondromas originating from the falx, the convexity dura, the tentorium, the choroid plexus, and the brain parenchyma have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Hardy et al [31] reported a patient with a survival period of 44 years after complete removal of a convexity chondroma. After subtotal resection, malignant degeneration of the tumor rest into chondrosarcoma has been reported [3,9]. Therefore, in cases with subtotal resection of the chondroma, long-term imaging follow-up with cerebral CT-scan or MRI may be necessary to early detect local invasion or recurrences [32].…”
Section: Discussionmentioning
confidence: 99%
“…Chondromas are infrequent brain tumors, with a very low incidence, estimated at 0.2-0.5% of all intracerebral tumors [1,2].The skull base synchondrosis represents the usual origin of chondromas [3],but, exceptionally, they develop from the convexital dura mater or the falx [4,5]. We present the case of a large intracranial chondroma, which arises from the falx cerebri.…”
Section: Introductionmentioning
confidence: 95%
“…5 Chondrosarcoma above the skull base has been reported to arise from the choroid plexus, dura mater or brain parenchyma. [6][7][8][9][10][11] Chondrosarcoma is subclassified into conventional, de-differentiated, clear cell and mesenchymal subtypes. The most common is the conventional subtype.…”
Section: Discussionmentioning
confidence: 99%